Language Variation in TikTok Social Media Platform Advertising Discourse: Its Use as Indonesian Language Teaching Material for Class VIII - Dafa Al Fauzan; Agus Budi Wahyudi (Universitas Negeri Semarang, 2025)
The use of Indonesian in the advertising discourse of the TikTok social media platform is adjusted to the language speakers. This study examines 1) the form of language, 2) the purpose of advertising discourse and 3) its use as open material for Indonesian. This method uses a qualitative research method with a descriptive design, because the data used is in the form of oral discourse. The object of this study is language variation in advertising discourse. The data collection technique uses the listening technique, the researcher listens to the advertising discourse on the TikTok social media platform and then notes each oral discourse that contains language variation. The data analysis technique uses the referential matching method. The data validation technique uses data triangulation. The results of the study show that the form of language and the purpose of the advertisement discourse are: 1) Indonesian and Javanese, 2) Indonesian and Balinese, 3) Indonesian and English, 4) Indonesian and Korean, 5) Indonesian and Japanese, 6) Indonesian and Italian, 7) Indonesian and Javanese and English, 8) Indonesian and Minang and Korean, 9) Indonesian and Japanese and English, 10) Indonesian and French and Italian and English and Japanese, and the purpose of the advertisement discourse is: 1) attracting attention, 2) attracting interest, 3) changing actions.